Characterization and selection of polymers for future research on enhanced oil recovery - de Melo, Maria; Lucas, Elizabete (Publishing House of Lviv Polytechnic National University, 2008)
Polymer flooding has been applied for petroleum recovery and the main results of this method are the effective increasing in oil production and the reduction of water circulation The objective of this work is to present a methodology for pre-selecting a polymer to be used in future research on enhanced oil recovery (EOR) by injecting polymer solution. A reservoir was selected and characterized. Seven samples of commercial partially hydrolyzed polyacrylamide (PHPA) were also selected and characterized. Polymer solutions were prepared and characterized in terms of filterability, viscosity, stability (under reservoir conditions) and mechanical degradation. Polymer-reservoir interaction was also investigated. The results showed that it is very useful to establish a methodology to pre-select the more suitable polymer for fluid injection operations in oil field. Besides, for the conditions used in this study, the best polymer presents hydrolysis degree of 30%, molar mass of 5?106 g /mol and intrinsic viscosity of 10 ml/g. Для підвищення ефективності виробництва нафти та зниження циркуляції води при видобутку нафти використовують нагнітання у свердловину полімерів. В роботі представлено методику попереднього вибору полімеру, який надалі буде використаний в дослідженнях, пов'язаних з видобутком нафти з вприскуванням полімерного розчину. Вибрано і охарактеризовано пластовий резервуар, а також сім зразків промислового, частково гідролізованого поліакриламіду. Приготовлений полімерний розчин охарактеризований на фільтрованість, в'язкість, стабільність та механічну стійкість. Досліджена взаємодія між полімером і резервуаром. Показано, що найкращі результати отримано при використанні полімеру, в якому ступінь гідролізу становить 30% молекулярна маса 5*106 г/моль і внутрішня в'язкість 10 мл/г.
Характеристика і вибір полімеру для майбутнього використання при видобутку нафти
Keywords: petroleum recovery; polymeric solutions; polymeric characterization; rock characterization; rheological behavior; filterability tests; static adsorption test; видобуток нафти; полімерні розчини; характеристика полімеру; характеристика пласту; реологічна поведінка; тест на фільтрованість; тест на статичну адсорбацію